Penerapan model pembelajaran talking stick untuk meningkatkan motivasi belajar peserta didik pada pembelajaran matematika kelas v sekolah dasar - Ayu Prasetyaningrum; Siti Istiyati; Tri Budiharto (Didaktika Dwija Indria, 2019)
This research is a classroom action research aimed at increasing learning motivation in Mathematics through the Talking Stick learning model for 5th grade students in Karanganyar in the 2018/2019 academic year. The subjects of this study were aclassteacherand 28 students from grade 5 elementary school students. The procedure of this study consists of 3 cycles, each cycle has 4 stages, namely planning, action, observation, and reflection. The data collection of this research was carried out by interviews, observations, learning motivation questionnaires, and document study techniques. The data validity used is construct validity and triangulation technique. This study uses interactive analysis (Miles and Huberman models) for data analysis. The results of the study after the action increased from the initial conditions were 7% to 54% in the first cycle, 75% in the second cycle, and 90% in the third cycle. Based on the results of this study, it can b econcluded that the motivation in learning mathematics in grade 5 elementary school students increased after the Talking Stick learning model was implemented.